(untitled) (Transport systems and technologies, 2021)
The article describes the production and use of crushed stone in Ukraine. The price factor of production and sale of crushed stone in the foreign countries is given and the comparative analysis with the Ukrainian producers is carried out. The dynamics of capacity and production of crushed stone products in Ukraine taking into account export and import components is given. It is established that the most capacious market is located in Zhytomyr region. It is noted that the share of crushed stone production of the enterprises located on the territory of the Regional Branch "South-Western Railway" is 44. It was found that only fruitful cooperation between two parties will get positive results, which will certainly increase railway traffic.